Educators’ and Parents’ Perspectives About Belonging in Early Years Education in Europe - Johansson, Eva Marianne; Walker, Sue; Lunn, Jo; Whiteford, Chrystal; Karlsudd, Peter; Puroila, Anna-Maija; Piskur, Barbara; Einarsdóttir, Jóhanna (International Journal of Early Childhood, 2024)
The overall goal of this project is to gain a broad picture of belonging and the politics of belonging in early education settings (In Norway, Sweden, Finland, and Iceland the children attend school from 6 or 7 years. In the Netherlands children attend compulsory school at 4 years of age. Using the terms early education settings and (pre)schools with parenthesis we refer to educational institutions (preschool, day-care, compulsory school) involving children between 4 and 6 years) in five European countries: Finland, Iceland, the Netherlands, Norway, and Sweden. By ‘belonging’ we refer to children´s sense of feeling safe and ‘at home’. By ‘politics of belonging’ we refer to societal structures and processes of safeguarding communities and their borders among children (and educators) in their early education settings. Educators (n = 648) and parents (n = 1,598) were surveyed about their perspectives about, and pedagogies for, belonging. Results indicated that, in general, parents and educators felt positively about belonging in their (pre)schools. Even so the study shows that experiences of belonging cannot be taken for granted, and a number of parents and educators worry about children being excluded and alienated. The study also revealed a relation between the educational level of educators and the complexity of pedagogic methods educators used to support children´s belonging in early education settings. publishedVersion